Early identification of DPAM in at-risk low-grade appendiceal mucinous neoplasm patients: a new approach to surveillance for peritoneal metastasis. Issue 1 (December 2016) - Foster, Jason; Sleightholm, Richard; Wahlmeier, Steve; Loggie, Brian; Sharma, Poonam; Patel, Asish
Abstract Background Disseminated peritoneal adenomucinosis (DPAM) patients often have a history of appendectomy with identification of an incidental mucinous neoplasm (low-grade appendiceal mucinous neoplasm (LAMN)). The rate of developing DPAM is not well established. Methods Twenty-two patients with incidental LAMN were identified and monitored with cancer markers and CT every 4–6 months. Laparoscopy with peritoneal washing was performed in patients either in the event of radiographic disease or after 12 months in absence of radiographic disease. The rate of detecting peritoneal metastasis was determined for CT scan and laparoscopy. Results Peritoneal metastasis was detected in 5 (23 %) patients. Occult disease was detected in four patients at laparoscopy without a detectable disease on CT scan. One patient developed radiographic progression at 6 months confirmed with laparoscopy. Four patients were treated with cytoreductive surgery (CRS)/HIPEC and one with CRS only. The 17 patients with negative laparoscopy remain disease free with a median follow-up of 50 months. Conclusions The rate of peritoneal metastasis in incidental LAMN patients was 23 %. Laparoscopy was the primary screening tool identifying occult metastasis. The median PCI of 7 was low, and all the patients underwent R0/R1 resections. This study revealed 1 in every 4.4 patients with LAMN may develop PMP. Longer follow-up and further patient surveillance is warranted.